2005
DOI: 10.1016/j.marpolbul.2005.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Butyltin compounds in a sediment core from the old Tilbury basin, London, UK

Abstract: Sections from a sediment core taken from the River Thames were analysed for butyl tin species using gas chromatography with species-specific isotope dilution mass spectrometry. Results demonstrated that in most samples tributyltin concentrations of 20 -60 ng/g accounted for <10% of the total butyl tin species present, which is in agreement with data from other sediment samples which were historically contaminated with tributyltin. Vertical distribution of the organotin residues with depth throughout the core, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The certified value of MBT for sediment PACS 2 has been shown to be debatable by a number of independent publications. The actual MBT concentration appears to be closer to 600 ng Sn g −1 (Scrimshaw et al 2005).…”
Section: Determination Of Butyltin(iv) Species In Marine Sediment Andmentioning
confidence: 84%
“…The certified value of MBT for sediment PACS 2 has been shown to be debatable by a number of independent publications. The actual MBT concentration appears to be closer to 600 ng Sn g −1 (Scrimshaw et al 2005).…”
Section: Determination Of Butyltin(iv) Species In Marine Sediment Andmentioning
confidence: 84%
“…Phenyltin concentrations are lower, between 0.5 and 49 ng Sn g −1 for MPhT, 0.2 and 8 ng Sn g −1 for DPhT, and 0.1 and 0.5 ng Sn g −1 for TPhT, while octyltins concentrations were lower than 0.5 ng Sn g −1 . Scrimshaw et al (2005) investigated the historical deposition of butyltins in bed sediments from the harbor in the River Thames (UK). Results from sediment cores demonstrated that in most samples, TBT concentrations of 20-60 ng Sn g −1 accounted for less than 10% of the total butyltin species present.…”
Section: Otc In Sediments Of the Sava Rivermentioning
confidence: 99%
“…Trisubstituted OTC, including TBT and TPhT, are among the most hazardous pollutants to enter aquatic ecosystems (Hoch 2001 EC 2000). Although OTC were intensively investigated in the marine environment (Coelho et al 2002;Díez et al 2005;Godoi et al 2003;Gomez-Ariza et al 2001;Harino et al 1999;Milivojevič Nemanič et al 2002Ščančar et al 2007), they are a rare subject of research in river sediments (Bancon-Montigny et al 2004;ICPDR 2002;Lacorte et al 2006;Scrimshaw et al 2005).…”
mentioning
confidence: 99%
“…Other areas of the Iberian Peninsula also show similar values as studied by Quevauviller et al (1989) in the Sado Estuarine System, western Portugal (TBT: 12-520 ng Sn g -1 dw) and by Gabrielides et al (1990) (TBT: 35-975 ng Sn g -1 dw) and Tolosa et al (1992) (TBT: 9260 ng Sn g -1 dw) in the Mediterranean region. The study of the levels of TBT in other European countries shows different values amongst locations: Chiavarini et al (2003) in the North West Sicilian coast in Italy (TBT: 3-27 ng Sn g -1 dw), Jacobsen (2000) in Danish harbours and marinas (TBT: 100-5,000 ng Sn g -1 dw) and Scrimshaw et al (2005) in the river Thames in United Kingdom (TBT: 1-60 ng Sn g -1 dw). In comparison with the ecosystems reported by these authors, the butyltin levels in the sediments along the Gulf of Cádiz suggest a relatively low contamination in general.…”
Section: Distribution Of Butyltins In Sedimentsmentioning
confidence: 99%